(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
This essay offers an analysis of the letter of credit from two perspectives, that of the Venezuelan Commercial Code and that of International Trade, for which an exhaustive study was made of the provisions contained in the code of commerce, of documents and related literary productions. with the letter of credit provided for in the Venezuelan mercantile legislation, in order to determine its nature, intervening subjects and characteristic elements; Likewise, the Uniform Rules and Uses Relating to Documentary Credits, known by their acronym in English UPC, issued by the International Chamber of Commerce, with the intention of establishing the definition, the persons involved, the route, its requirements and the The form adopted by the documentary letter of credit used mostly in international sales. In this regard, special reference was made to the terms of international commerce called INCOTERMS due to its close link with the documentary letter of credit. It was concluded although equals, both letters of credit are absolutely different in their nature, operation and regulation; and that when Venezuela currently refers to a letter of credit, it is the one regulated by the International Chamber of Commerce.